High TG to HDL ratio plays a significant role on atherosclerosis extension in prediabetes and newly diagnosed type 2 diabetes subjects. Issue 2 (20th July 2020) - Scicali, Roberto; Giral, Philippe; D'Erasmo, Laura; Cluzel, Philippe; Redheuil, Alban; Di Pino, Antonino; Rabuazzo, Agata Maria; Piro, Salvatore; Arca, Marcello; Béliard, Sophie; Purrello, Francesco; Bruckert, Eric; et al.
Abstract: Aims: We investigated the role of TG to HDL ratio (TG/HDL) on atherosclerosis extension, defined as presence of coronary artery calcium (CAC), carotid and femoral plaque, in prediabetes or newly diagnosed type 2 diabetes (T2D). Methods: We performed a retrospective, cross‐sectional, single centre study involving 440 prediabetes or newly diagnosed controlled T2D subjects. Participants underwent CAC analysis by computed tomography and carotid and femoral plaque evaluation by ultrasonography and were stratified in high TG/HDL (H‐TG/HDL) or low TG/HDL (L‐TG/HDL) group according to TG/HDL median value. We estimated atherosclerosis extension according to the number of involved vascular districts. Results: CAC was higher in the H‐TG/HDL group than L‐TG/HDL group (29.15 [0.0‐95.68] vs 0.0 [0.0‐53.97] AU, P < .01) and CAC > 0 was more prevalent in the H‐TG/HDL group than L‐TG/HDL group (64.5% vs 45%, P < .001). Femoral atherosclerosis was higher in the H‐TG/HDL group than L‐TG/HDL group (57.3% vs 43.6%, P < .01). H‐TG/HDL group exhibited a lower prevalence of subjects with 0‐TWP compared to L‐TG/HDL group (21.8% vs 38.6%, P < .01) and higher percentages of subjects with 2‐TWP or 3‐TWP than L‐TG/HDL group (for 2‐TWP 29.5% vs 21.5%, P < .05; for 3‐TWP 32.7% vs 20.9%, P < .01). Multiple logistic regression analysis showed that a H‐TG/HDL was inversely associated to 0‐TWP ( P < .05) and positively associated with 2‐TWP ( P < .05) and 3‐TWP ( P < .01). Conclusions: Our data suggest that TG/HDL is a marker of increased atherosclerotic extension in prediabetes and newly diagnosed T2D and may be useful to identify subjects with a higher cardiovascular risk profile.